GROUP COOPERATIVE LEARNING IN UNIVERSITY ADVANCED MATHEMATICS - Luo, Zhijun (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
Advanced Mathematics is one of the most important and fundamental courses for students of engineering and science. In this paper, we consider how to enhance advanced mathematics teaching. Group cooperative learning is applied to the advanced mathematics classroom; the traditional teaching mode can be transformed in student-cantered environment so that students can study with each other under relaxing circumstances. It can enhance learners study motivation, foster their self-esteem and develop their interpersonal skills. Keywords: Advanced Mathematics research; Group cooperative learning; Assessment